Situation of Food Sanitation of Street Food in The Night Market Food of Chiang Mai Province - Rithmanee, Thanyanun; Kongkaew, Sikaret (YRU Journal of Science and Technology, 2023)
The study of the situation of street food sanitation in the night market food of Chiang Mai province consisting of 37 street foods for physical, chemical and biological that helps to improve the quality of street food and the safety of the health of consumers in the province and tourists. This research has been collected and evaluated using an assessment checklist 12 items for food sanitation requirements by the department of health. The training course has been set and the questionnaires have been applied to test the food handlers. These caused the food handlers have gained more knowledge and more understanding about food sanitation. The results found that entrepreneurs have better food sanitation management. Examination of contaminants in food by using the food test kit, such as borax, formalin, sodium hydrosulfite, salicylic acid, and total polar compounds in repeatedly used cooking oil was analyzed for the food contaminants recently. The result found that formalin contaminated in crispy pickled squid and fresh squid only 1 street food shop. The demonstrated results found that the contaminated samples were found on food handlers 28.57%, kitchen utensils 11.61% and food samples 31.67%. Thus, entrepreneurs should manage to improve street foods to maintain a high level of sanitation and standards for the consumers to be confidence to take the street foods for their meal.